Online Supermarket Web Application - Wijegunarathna K.P.S.G.G; Amarasinghe P.P.S; Judemal D.J.M.D.J.S; Vernan S.J; D.I De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
The main purpose of this paper is to present facts about a web application created for a supermarket. Two of the main problems faced by consumers today are lack of time to come and buy goods and transportation problems. By using this web application, customers can save the cost and time of visiting the supermarket. Customers who come to the supermarket using this web application will have the facility of ordering the products they need from home without going to the supermarket and having them delivered to their homes. Customers also get the opportunity to check the order status when they have ordered a product through this web application. Admin can add products to the system using the admin dashboard. Those added products will be displayed to the customers. After registering in the system, a customer can purchase goods. By entering the address of the place where customer wants to bring the purchased product, customer can bring the product to the relevant location. This web application is user-friendly and meets most of the requirements of customers and staff.